What Gives Life to Large System Change?. (September 2020) - Waddock, Sandra; Kuenkel, Petra
This article argues that the capacity to create the large system change needed to deal with "grand challenges" like the Sustainable Development Goals, sustainability, or climate change can be enhanced by understanding and applying a core set of principles, drawn from multiple sources and levels of analysis that have explored the question of "what gives life." These sources all—albeit in different ways—apply the question, what "gives life" to different types of systems, and how this relates to the (so far as we know) uniquely human capacity for reflection. We identify six principles that "give life" to systems—intentional generativity, permeable containment, emerging novelty, contextual interconnectedness and requisite diversity, mutually enhancing wholeness, and proprioceptive consciousness—then provide guidance for change agents and scholars, as well as an illustrative example of the principles in action. These six principles provide a foundation for thinking about how to create flourishing human systems in organizations, social change, and global sustainability transformation.